Analisis Masalah Umum dan Spesifik Penelitian Skripsi yang Menggunakan Model Discovery Learning di Sekolah Dasar (Studi Literatur) - Desyandri Desyandri; Reza Husni (Universitas Negeri Padang, 2020)
This literature research aims to analyze problems in integrated thematic learning in the use of discovery learning models in elementary schools. This analysis is motivated by the many thesis research problems that have not resulted from the review process of previous research findings and observations comprehensively. The problems raised were limited to seeing the conditions of learning in the field in a simple manner. The research object was 25 articles of thesis research results. Based on the results of the analysis and synthesis of 25 thesis research articles, there were 13 (52%) articles that listed and disclosed problems in general and 12 (48%) articles listed and revealed specific research problems. This shows that there are still many problem descriptions revealed in thesis research that use general problem categories and are not directly related to alternative solutions used to solve learning problems in elementary schools.